Konsep Ganjaran (TsawÄb) Sebagai Alat Pendidikan Menurut Al-Qurâ€™an - Hasibuan, Hamdan (IAIN Padangsidimpuan, 2020)
Deserts is one of the education appliance. Become, by itself intend deserts is as a means of to educate child so that child can feel to like because deed or its his/its get appreciation. Generally, child know that work or his/its deed which cause he get deserts is goodness. Education appliance is matter which do not just only load the condition of conducive executing of educative work, but can in the form of situation or deed, causing spirit of newly to educative participant in reaching the target of education. Allah also often wear deserts as motivation to human being to do to kindliness in laid open Alquran with term tsawÄb.